Analysis of the Impact of Sustainability Report Disclosure on the Company's Financial Performance - Daffa Amaansyah Samosir; Aina Zahra Parinduri (Jurnal MANDIRI: Ilmu Pengetahuan, Seni, dan Teknologi, 2025)
This study examines the influence of economic, social, and environmental performance disclosures in Sustainability Reports on financial performance (Return on Assets (ROA) and Return on Equity (ROE)) in a sample of listed banking companies that use GRI standards in their sustainability reports, for the period 2022-2024. Using a quantitative approach with secondary data and panel data regression analysis, the independent variables are the Economic Disclosure Index (ECDI), Social Disclosure Index (SODI), and Environmental Disclosure Index (ENDI) based on GRI Standards 2021. The results show that the disclosure of Sustainability Reports simultaneously has a significant effect on both ROA and ROE. However, partially, only economic performance disclosure (ECDI) has a significant positive effect on ROA and ROE, while social performance disclosure (SODI) and environmental performance disclosure (ENDI) do not have a significant effect on either ROA or ROE. The firm size variable as a control has a significant positive effect on ROA and ROE. This study concludes that comprehensive disclosure in Sustainability Reports collectively contributes to the increase in ROA and ROE, supporting Legitimacy Theory.